2015
DOI: 10.3390/w7020398
|View full text |Cite
|
Sign up to set email alerts
|

Benthic Uptake Rate due to Hyporheic Exchange: The Effects of Streambed Morphology for Constant and Sinusoidally Varying Nutrient Loads

Abstract: Hyporheic exchange carries reactive solutes, which may include biological oxygen demand (BOD), dissolved oxygen (DO) and reactive dissolved inorganic nitrogen (Nr), into the sediment, where biochemical reactions consume DO. Here, we study the impact of streambed morphology, stream-reactive solute loads and their diel oscillations on the DO benthic uptake rate (BUR) due to hyporheic processes. Our model solves the hyporheic flow field and the solute transport equations analytically, within a Lagrangian framewor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…As a water parcel exits the HZT and returns to the stream, its final nitrate concentration (denoted here by the function CHZTnormalNnormalO3true(τ;"chemistry"true), units mol m −3 ) will depend on the water parcel's travel time through the hyporheic zone ( τ, units s) conditioned on subsurface biogeochemical reactions that consume and produce nitrate (denoted here by the shorthand “chemistry”). Provided there is no mixing of mass across or within HZTs (i.e., mass transport occurs only by advection through the HZT, discussed further in section 2.2), mass balance over a single submerged and periodic bed form yields the PASS model for nitrate uptake velocity [ Rutherford et al ., ; Grant et al ., ; Azizian et al ., ; Tonina et al ., ]: vf=qHtrue[trueC¯HZTnormalNnormalO31true] trueC¯HZTnormalNnormalO3=1CnormalSnormalNnormalO30CHZTNO3(τ;chemistry)×E(τ)dτ …”
Section: Pumping and Streamline Segregation (Pass) Model For Nitrate mentioning
confidence: 99%
See 1 more Smart Citation
“…As a water parcel exits the HZT and returns to the stream, its final nitrate concentration (denoted here by the function CHZTnormalNnormalO3true(τ;"chemistry"true), units mol m −3 ) will depend on the water parcel's travel time through the hyporheic zone ( τ, units s) conditioned on subsurface biogeochemical reactions that consume and produce nitrate (denoted here by the shorthand “chemistry”). Provided there is no mixing of mass across or within HZTs (i.e., mass transport occurs only by advection through the HZT, discussed further in section 2.2), mass balance over a single submerged and periodic bed form yields the PASS model for nitrate uptake velocity [ Rutherford et al ., ; Grant et al ., ; Azizian et al ., ; Tonina et al ., ]: vf=qHtrue[trueC¯HZTnormalNnormalO31true] trueC¯HZTnormalNnormalO3=1CnormalSnormalNnormalO30CHZTNO3(τ;chemistry)×E(τ)dτ …”
Section: Pumping and Streamline Segregation (Pass) Model For Nitrate mentioning
confidence: 99%
“…Indeed, based on 15 NH 1 4 stream seeding studies, Peterson et al [2001] concluded that ammonium is removed primarily by assimilation and sorption to sediments, and ''secondarily by nitrification.'' These model limitations can be Water Resources Research 10.1002/2016WR020048 addressed by increasing model complexity, for example by adding: (1) an additional term to the mass balance equation for nitrate (equation (4b)) to account for the kinetics of nitrate assimilation [e.g., see Birgand et al, 2007]; (2) a rate equation to the biokinetic model for the evolution of dissolved and/or particulate organic carbon concentration with travel time [Zarnetske et al, 2012]; and (3) additional terms to the mass balance equation for ammonium (equation (4c)) to account for adsorption and assimilation [Thibodeaux and Mackay, 2011].…”
Section: 1002/2016wr020048mentioning
confidence: 99%
“…Stream water temperature plays an important role in aquatic ecosystems and is an important cue for organism behavior (Isaak, Wollrab, Horan, & Chandler, ; Jobling, ; Rice, Breck, Bartell, & Kitchell, ; Rieman et al, ), fish metabolism (Forseth & Jonsson, ; Isaak, Young, Nagel, Horan, & Groce, ; Mesa, Weiland, Christiansen, & Sauter, ; Railsback & Rose, ), and growth rates (Brett, ; Crozier, Zabel, Hockersmith, & Achord, ; Xu, Letcher, & Nislow, ). Stream water temperature controls dissolved oxygen concentrations, which may affect water quality and biogeochemically reactive solutes (Marzadri, Tonina, & Bellin, ; Marzadri, Tonina, & Bellin, ; Tonina, Marzadri, & Bellin, ; Webb, Hannah, Moore, Brown, & Nobilis, ) whereas high stream water temperatures may negatively affect industrial activity (Boogert & Dupont, ; Null, Viers, Deas, Tanaka, & Mount, ; Vliet, Vogele, & Rubbelke, ; Vliet, Yearsley, Ludwig et al, ). These studies indicate the value of accurate estimates of daily stream water temperatures for dam and water resource managers, ecologists, economists, and decision makers.…”
Section: Introductionmentioning
confidence: 99%
“…N 2 O is one of the most important greenhouse gases contributing, for example, to the stratospheric ozone destruction (Ravishankara et al, 2009). Current models of DO and DIN dynamics in the HZ assume either constant or periodically varying in-stream loads and constant reaction rate coefficients (Tonina et al, 2015), thus ignoring the impact of their variability Water Resources Research 10.1029/2018WR022525 on the overall dynamics. Uncertainty about the role of these driving forces (boundary and initial conditions) on the overall N 2 O emissions, together with paucity of available data (field measurements are often time-consuming and costly; Baulch et al, 2011), motivates the development of quantitative methods that leverage the knowledge of appropriate physical and chemical laws to statistically characterize the global N 2 O budget.…”
Section: Introductionmentioning
confidence: 99%